TINGKAT KESUKAAN MASYARAKAT TERHADAP TEH DAUN GAHARU (Aquilaria mallacensis Lamk.) DIBANDINGKAN TEH LAIN YANG BEREDAR DI PASARAN - Roy Brema Ginting; Ridwanti Batubara; Herawaty Ginting (Program studi Kehutanan USU, 2015)
Agarwood leaves contain chemical compounds such as flavonoid, flavons, flafonols and isoflavones that can be use as a brewed beverage. That has a function as an antioxidant. The objective of this research was to determine the consumen preference on agarwood leaf tea compared other tea on the market. Types of tea on the market were used as a comparison is C. cinencis tea and soursop leaf tea. This study was made in 4 stages i.e plant sampling, making agarwood leaf tea, determination of tannin content, and evaluation of consumen preference on agarwood leaf tea by hedonic test on taste, aroma, and colour using 1-5 scale i.e (very unlike-very like) for agarwood leaf tea at 0 and 2 month of storage. The highest to lowest of tannin content was found in C. cinencis tea (0,5464%),agarwood leaf tea (0,2571%), and soursop leaf tea (0,0643%). In the 0 month storage preference level of society against agarwood leaf tea is favored as seen from the scores obtained in terms of taste, aroma and colour that is 3,72; 3,10; 2,42. For the agarwood leaf tea that has been storage for 2 month, agarwood leaf tea still favored where the score for taste, aroma and colour were 3,34; 3,04; 2,36.Key words: agarwood tea, consumen preference, and hedonic test